1016 Wolf in sheep skin: serious neurological condition presenting as refractory Restless Leg Syndrome. (12th April 2019) - Neupane, Pritam; Kulwin, Charles G; Sigua, Ninotchka; Manchanda, Shalini; Bodkin, Cynthia
Abstract: Introduction: Restless leg syndrome (RLS) is common in patients with known spinal cord injury but spinal cord disease presenting as RLS to our knowledge has not been reported. Here we present a case of progressive cervical spondylotic myelopathy who presented with refractory RLS. Report of case: A 58 years old desperate man with history of obstructive sleep apnea, degenerative disc disease of lumbosacral and cervical spine, status post lumbosacral spine surgery in the remote past and RLS of 12 years duration presented with six months history of severe worsening of RLS symptoms. Review of systems was positive for several falls recently that he attributed to the extreme restlessness of his legs. He had been on pramipraxole for years but this was no longer effective. Another physician had switched him to ropinirole without clinical benefit. His physical examination demonstrated wide based gait with spasticity in the legs. He was given gabapentin and MRI of his cervical spine was obtained. While he had no response to gabapentin, his MRI showed severe cervical stenosis with multilevel spinal cord compression and cord signal change. He was urgently referred to neurosurgery for decompression and had complete resolution of RLS symptoms at one month post-operative follow up. Conclusion: While RLS is very common and is a clinical diagnosis, it is important to consider secondary causes of RLS and to perform a neurological examination. It was solely the history of falls and exam findings of myelopathy that led to the diagnosis of the serious spinal cord lesion in this patient. His failure to respond to usual treatments, chronic nature of RLS with acute worsening and complete resolution of his symptoms after spinal decompression all confirm that his RLS was the symptom of worsening cervical spondylotic myelopathy. It is important to consider these mimickers in the evaluation of patients with RLS.